Crystal structure and theoretical study of N,N-bis[(5-chloro-2-oxo-2,3-dihydrobenzo[d]oxazol-3-yl)methyl]-2-phenylethanamine - Aydın, Abdullah; Soyer, Zeynep; Akkurt, Mehmet; Büyükgüngör, Orhan (International Union of Crystallography (IUCr), 2018)
In the molecular structure of the title compound, C24H19Cl2N3O4, the three C atoms of the central N,N-dimethylmethanamine moiety are bonded to the N atoms of the two 5-chloro-1,3-benzoxazol-2(3H)-one groups and to the methyl C atom of the methylbenzene group. One of the nine-membered 2,3-dihydro-1,3-benzoxazole rings and the phenyl ring are almost parallel to each other, making a dihedral angle of 5.30 (18)°, but they are almost normal to the mean plane of the other nine-membered 2,3-dihydro-1,3-benzoxazole ring, subtending dihedral angles of 89.29 (16) and 85.41 (18)°, respectively. The crystal structure features C—H...O hydrogen bonds and π–π stacking interactions [centroid-to-centroid distances = 3.5788 (19) Å, slippage = 0.438 and 3.7773 (16) Å, and slippage = 0.716 Å].
Keywords: crystal structure; HOMO; LUMO; Crystallography; QD901-999; semi-empirical CNDO /2 method; semi-empirical CNDO/2 method; ,3-dihydro-1,3-benzoxazole ring; Research Communications; 13. Climate action; 3. Good health